Official Languages Recognition Program (OLRP) - Accreditation Canada (2022)
Accreditation Canada’s Official Languages Recognition Program (OLRP) supports and awards organizations that are committed to improving access to health and social services in official languages. This brochure answers questions such as: - How does the program work? - How does this program integrate with our current language accessibility efforts? - Who developed this program? - Why is this the right time to participate? - How much does it cost to participate in the program?

Programme de reconnaissance des langues officielles (PRLO) - Agrément Canada (2022)
Le Programme de reconnaissance des langues officielles (PRLO) d'Agrément Canada appuie et certifie les organismes qui sont engagés à améliorer l'accès aux services de santé et services sociaux en langues officielles. Ce feuillet d'information à l'intention des fournisseurs de services répond aux questions suivantes: - Comment le programme fonctionne‐t‐il ? - Comment ce programme s'intègre-t-il à nos efforts actuels d'accessibilité linguistique ? - Qui a élaboré ce programme ? - Pourquoi est-ce le bon moment de participer ? - Quel est le coût pour participer au programme ?

Non-official language concordance in urban Canadian medical practice: Implications for care during the COVID-19 pandemic - Ariste, Ruolz; di Matteo, Livio (Healthcare Policy, 2021)
Language barriers can reduce access to medical and virtual care. Although the topic of healthcare professionals and linguistic minorities has been studied in Canada, it has mainly been done for official languages (i.e., English and French). Non-official languages (NOLs) have not been explored previously in the healthcare system at the pan-Canadian level. The objective of this study is to determine to what extent NOLs spoken by physicians relate to those of Canadian ethnic groups and are an enabler of access to care. Using data from the Canadian Institute for Health Information (CIHI) and Statistics Canada, we found an imbalance in the physician-to-population NOL ratios in Montreal and, to a lesser extent, Vancouver.

The debate on staff language competences and the use of official languages in the Balearic Islands health system - Ballester Cardell, Maria; Marí Mayans, Isidor (Linguistic Minorities and Society, 2021)
The Spanish Constitution of 1978 and the Statute of Autonomy of the Balearic Islands of 1983 established the official nature of both Spanish and Catalan and entrusted public authorities with guaranteeing the right of citizens to use one or the other on an equal footing. Subsequent to the language legislation of 1986, the legal framework of Catalan has varied depending on the majority party that forms a government. The debate stirred up by these regulations demonstrates the difficulties in ensuring real equality between official languages, when social initiatives cannot translate into sufficient political support and the national political context is hostile. The article explores this debate and discusses recent regulations surrounding the official languages competencies of health system staff, from the direct experience of the authors, as members of two consultative institutions on legal and sociolinguistic matters. Keywords: language rights, official language, language competence, medical communication, health services

Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

Distance, access and equity: A cross-sectional geospatial analysis of disparities in acess to primary care for French-only speakers in Ottawa, Ontario - Belanger, Christopher; Carr, Kady; Peixoto, Cayden; Bjerre, Lise M. (CMAJ Open, 2023)
Background: Although language concordance between patients and primary care physicians results in better quality of care and health outcomes, little research has explored inequities in travel burden to access primary care people of linguistic minority groups in Canada. We sought to investigate the travel burden of language-concordant primary care among people who speak French but not English (French-only speakers) and the general public in Ottawa, Ontario, and any inequities in access across language groups and neighbourhood ruralities. Methods: Using a novel computational method, we estimated travel burden to language-concordant primary care for the general population and French-only speakers in Ottawa. We used language and population data from Statistics Canada’s 2016 Census, neighbourhood demographics from the Ottawa Neighbourhood Study, and collected the main practice location and language of primary care physicians from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Results: We included data from 869 primary care physicians and 916 855 patients. Overall, French-only speakers faced greater travel burdens than the general population to access language-concordant primary care. Median differences in travel burden were statistically significant but small (median difference in drive time 0.61 min, p < 0.001, interquartile range 0.26–1.17 min), but inequities in travel burden between groups were larger among people living in rural neighbourhoods.

Patient and Provider Satisfaction With a Geomapping Tool for Finding Community Family Physicians in Ontario, Canada: Cross-Sectional Online Survey Study. - Belanger, Christopher; Peixoto, Cayden; Francoeur, Sara; Bjerre, Lise M. (JMIR formative research, 2024)
Background: Language-concordant health care, or health care in a patient’s language of choice, is an important element of health accessibility that improves patient safety and comfort and facilitates an increased quality of care. However, prior research has found that linguistic minorities often face higher travel burdens to access language-concordant care compared to the general population. Objective: This study intended to assess patient experiences and satisfaction with an online interactive physician map that allows patients to find family physicians who speak their preferred language in and around Ottawa, Ontario, Canada, as a means of identifying areas of improvement. Methods: This study used an online survey with questions related to user satisfaction. Responses to Likert-scale questions were compiled as summary statistics and short-answer responses underwent thematic analysis. The study setting was Ottawa and Renfrew County, Ontario, and the surrounding region, including the province of Quebec. Results: A total of 93 respondents completed the survey and self-identified as living in Ontario or Quebec. Overall, 57 (61%) respondents were “very satisfied” or “somewhat satisfied” with the map, 16 (17%) were “neither satisfied nor dissatisfied,” and 20 (22%) were “very dissatisfied” or “somewhat dissatisfied.” We found no significant differences in satisfaction by preferred language, age group, physician attachment, or intended beneficiary. A total of 56 respondents provided short-answer responses to an open-ended question about map improvements. The most common specific suggestion was to show which physicians are accepting new patients (n=20). Other suggestions included data refreshes (n=6), user interface adjustments (n=23), and additional languages (n=2). Some participants also provided positive feedback (n=5) or expressed concern with their inability to find a family physician (n=5). Several comments included multiple suggestions. Conclusions: While most patients were satisfied with the online map, a significant minority expressed dissatisfaction that the map did not show which family physicians were accepting new patients. This suggests that there may be public interest in an accessible database of which family physicians in Ontario are currently accepting new patients.

Pratique # 24 : Communauté accueillante 2.0 et Formation Les Communautés de Pratique : une démarche collaborative pour accroître l’offre de services en français (Ontario) - Benoît, Josée; Dagnogo, Djenaba Sarah; Renaud, Alexandre (2023)
fs-ref-orig: Benoît, J., Dagnogo, D.S. & Renaud, A. (2023, mise à jour 2025). Pratique # 24 : Communauté accueillante 2.0 et Formation Les Communautés de Pratique : une démarche collaborative pour accroître l’offre de services en français (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html fs-code-orig: Benoit-2025f

Pratique # 18 : Le plan de contingence du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)
fs-ref-orig: Benoît, J., Dagnogo, D.S., Savard, J. & Savard, S. (2021, mise à jour 2025). Pratique # 18 : Le plan de contingence du Réseau de santé Horizon (Nouveau-Brunswick). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops. ca/repertoire_pratiques_novatrices.html fs-code-orig: Benoit-2025b

Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)
fs-ref-orig: Benoit, J., Dagnogo, D.S., Savard, J., & Savard, S. (2021, mise à jour 2025). Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/ repertoire_pratiques_novatrices.html. fs-code-orig: Benoit-2025c

Santé et mieux-être des élèves francophones au Nouveau-Brunswick (Canada) - Boivin, Nathalie; Foulem, Ghislaine; Desjardins, Isabelle Perron (La Revue de Santé Scolaire et Universitaire, 2025)

Santé de la population francophone et anglophone âgée de 65 ans et plus de l’Ontario [affiche] - Bouchard, Louise; Batista, Ricardo; Duong, Patrick; Sauvé-Schenk, Katrine; Lizotte, Mathieu (2025)

Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes - Bouchard, Louise; Batista, Ricardo; Reaume, Michael (Université d’Ottawa et Institut du savoir Montfort, 2021)
fs-ref-orig: Bouchard, L., Batista, R. et Reaume, M. (2021). Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes. Université d’Ottawa et Institut du savoir Montfort. fs-code-orig: Bouchard-2021a

Les données linguistiques pour la recherche et la planification en santé : possibilité et limites pour l'étude des francophones en situation minoritaire - Bouchard, Louise; Lizotte, Mathieu (Minorités linguistiques et société, 2024)
Malgré de remarquables avancées de recherche sur la problématique de la santé en contexte francophone minoritaire, la disponibilité de variables linguistiques complètes et cohérentes dans les bases de données nationales de santé demeure lacunaire et fragmentée, constituant un défi considérable pour l’étude de la santé des membres des communautés francophones en situation minoritaire (CFSM) et la planification de services adaptés à cette population dispersée. Cet article offre un bilan exhaustif des possibilités et des limites des données disponibles permettant l’étude de la santé des CFSM. Ce faisant, il met en lumière une série de problèmes méthodologiques, dont le manque de données pertinentes, l’absence de variables standardisées et les faibles effectifs pour l’analyse régionale, entre autres. Ces lacunes entravent considérablement la capacité des chercheuses et chercheurs à étudier les conditions et les besoins spécifiques des CFSM en ce qui concerne la santé et la planification de la santé. Mots-clés : données linguistiques, problèmes méthodologiques, francophone, minorité, quantification

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

La santé en contexte francophone minoritaire au Canada : 20 ans de recherche: Introduction - Bouchard, Louise; Savard, Jacinthe; Dumond, Morgan (Minorités linguistiques et société, 2024)

Instantané de recherche : portrait de la santé mentale des Canadiens francophones en situation minoritaire - CAMH-Evidence Exchange Network (2020)

La recherche en temps réel : projet ECHO pour francophones - Détermination des besoins des fournisseurs de services desservant les communautés franco-ontariennes afin de créer un programme de formation en français sur le traitement des dépendances - CAMH-Evidence Exchange Network (2023)
fs-ref-orig: CAMH-Evidence Exchange Network. (2023). La recherche en temps réel : projet ECHO pour francophones - Détermination des besoins des fournisseurs de services desservant les communautés franco-ontariennes afin de créer un programme de formation en français sur le traitement des dépendances. https://kmb.camh.ca/fr/eenet/documentation/la-recherche-en-temps-reel-projet-echo-pour-francophones fs-code-orig: CAMH-Evidence Exchange Network-2023a

Research as it Happens : ECHO project for Francophones - Assessing the needs of service providers working with Franco-Ontarian communities to create a French-language, substance use management training program - CAMH-Evidence Exchange Network (2023)

Évaluer le potentiel de soins linguistiquement concordants pour les francophones de l’Ontario : une étude populationnelle transversale. - Carr, Kady; Batista Moliner, Ricardo; Fitzgerald, Michael; Lamontagne, Sophie; Bader Eddeen, Anan; Timony, Patrick E.; Bédard, Daniel; Gauthier, Alain; Prud’homme, Denis; Landry, Josette-Renée; Chomienne, Marie-Hélène; Denis-Leblanc, Manon; et al. (Minorités linguistiques et société, 2024)
Cette étude a utilisé les données sur les médecins, la facturation et le recensement de 2016 dont dispose l’ICES pour examiner l’accès potentiel à des médecins de famille francophones pour les francophones résidant dans 1 643 aires de diffusion agrégées (ADA) de l’Ontario. L’Ontario compte 550 280 francophones, soit 4,1 % de sa population. Nous avons identifié 8 199 médecins de famille, parmi lesquels 1 169 se sont autodéclarés francophones. Le ratio provincial global pour les francophones était de 2,12 médecins par 1 000 résidentes et résidents, comparativement à un ratio de 0,66 pour les anglophones. Dans les ADA où les francophones étaient majoritaires, le ratio pour les francophones était inférieur au ratio pour les anglophones (0,63 vs 2,02), alors que dans toutes les autres ADA, le ratio francophone était plus élevé (3,46 vs 0,62 dans les 83,4 % des ADA où les francophones représentaient >0 % à <5 % de la population). Huit ADA du Nord-Est et de l’Est de l’Ontario présentaient un déficit relatif important de médecins de famille francophones par rapport au ratio provincial. Ces résultats donnent un aperçu des régions qui pourraient bénéficier de programmes visant à éliminer les barrières linguistiques. Mots-clés : Concordance linguistique, médecins de famille, accès aux soins primaires, francophones, Ontario

Plaidoyer pour la santé - Un guide pratique - Chaput, Sarah (Réseau francophone international pour la promotion de la santé, 2022)

Le moment Monfort dans la francophonie canadienne. - Charbonneau, François (Presses de l’Université d’Ottawa, 2024)

The principle of minority protection and language rights in Canada: The secession reference’s legacy - Chouinard, Stéphanie (Journal of Parliamentary and Political Law, 2021)

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Une innovation réussie et durable au sein d’un réseau de santé, soit un hôpital et centre de santé communautaire en région rurale au Canada - Collin, Stéphanie; Michaud, Nancy; Ringuette, Claudie (Revue francophone sur la santé et les territoires, 2024)
Dans le monde, les décideurs publics tentent de trouver des arrangements structuraux pour améliorer la performance des systèmes de santé. La stratégie de régionalisation a été privilégiée depuis quelques décennies par une majorité des provinces canadiennes. Dans cet article, nous nous penchons sur les dynamiques relationnelles entre les acteurs associés à une régie régionale de la santé et leur influence sur la naissance et l’adoption d’une pratique innovante, soit un hôpital et centre de santé communautaire en région rurale. Une méthode de recherche qualitative a été retenue et la collecte de données a été effectuée par le biais d’entretiens semi-dirigés, de groupes de discussion, ainsi qu’une analyse documentaire. L’émergence et la pérennité d’une pratique innovante nécessitent une définition de la santé qui fait consensus, la présence d’entrepreneurs institutionnels et une redéfinition des rôles et responsabilités entre l’autorité centrale et les acteurs locaux. La mise en œuvre d’une gouvernance collaborative est également requise.

Une question de respect et de sécurité : l’incidence des situations d’urgence sur les langues officielles - Commissariat aux langues officielles (Gouvernement du Canada, 2020)

La discordance linguistique. L'intervenant et le patient ne parlent pas la même langue ou ne peuvent pas communiquer adéquatement [infographie] - Consortium national de formation en santé (2022)

La mobilisation des connaissances en santé dans les CFSM [infographie] - Consortium national de formation en santé (2021)

English-language Health and Social Services Access in Québec. Comparison 2019-2023 - CROP (Community Health & Social Services Network, 2023)

L’accès en anglais aux services de santé et aux services sociaux au Québec. Version française du rapport comparatif 2023-2019 - CROP (Community Health & Social Services Network, 2024)

Les Canadiens partiellement français sont susceptibles à une augmentation des facteurs de risque cardiovasculaire : une étude de cohorte rétrospective basée sur la population - Daccache, J.; Savoury, M.; Yam, Y.; Chow, B. J. M. (Annales de Cardiologie et d'Angéiologie, 2020)
Introduction Grâce à diverses recherches menées dans le passé, il a été démontré que le Québec est la province avec les taux d’infarctus aigü du myocarde (IAM) et la prévalence des facteurs de risque cardiovasculaire les plus élevés au Canada. Cette étude proposée effectuera une analyse rétrospective sur les populations caucasiennes, afin d’analyser les facteurs de risque cardiovasculaire dans les populations partiellement francophones par rapport aux Canadiens-Français et non-Français. En outre, nous analyserons de près les deux sexes des populations susmentionnées. Méthode Cette étude de cohorte rétrospective, basée sur la population, a été réalisée en utilisant le registre de l’ACTC de l’Institut de cardiologie de l’Université d’Ottawa (ICUO). Les participants sont des patients de race blanche de tout âge, qui sont venus à l’ICUO pour une angiographie par tomodensitométrie, entre 2006 et 2018, et qui ont donné leur consentement éclairé. SPSS a été utilisé pour comparer les différentes populations (Canadiens-Français [CF], Canadiens partiellement Français [CPF], et Canadiens non-Français [CNF]) et les différents sexes. Résultats La population des CPF ressemble plus à celle des FC, ayant une incidence plus élevée de facteurs de risque cardiovasculaire tels que le tabagisme, la dyslipidémie et le diabète de type 2. Interprétation Nos résultats suggèrent que les CPF, comme les CF, pourraient bénéficier d’une éducation plus intensive et de techniques de modification du mode de vie.

Accès aux services en santé dans la langue officielle de leur choix par les minorités francophones hors Québec. Analyse de données secondaires - Diaz Pinsent Mercier Research Inc (Consortium national de formation en santé, 2021)

Vers une amélioration de la prestation de services de santé pour les Franco-Ontariens - Doucet, Pascale-Anne. M.; Gorham, Robyn; Hunt, Elena (Journal de recherche interdisciplinaire, 2021)
Malgré le statut de dualité linguistique du Canada, la communauté francophone continue d’être laissée pour compte par les autorités du pays. Plus spécifiquement, l’étendue et l’accès restreints des services de santé offerts aux francophones en Ontario posent un grave danger pour cette population. Les établissements qui dispensent des services de santé continuent d’ignorer les politiques de soins existantes. Cette situation impose plusieurs actions au niveau fédéral, législatif et communautaire nécessaires afin d’assurer la garantie bilingue promise à la population canadienne. Parmi celles-ci, il faut augmenter la présence francophone dans les groupes décisionnels pour assurer la conception et l’établissement de programmes et services de santé axés sur les besoins uniques et distincts des franco-ontariens. Par ailleurs, l’engagement financier fédéral envers des organismes communautaires francophones est essentiel afin de fournir plus de services de santé en français, surtout dans les communautés nordiques et rurales de la province. Finalement, la subvention gouvernementale de futures recherches sur la santé des francophones est nécessaire puisque celles-ci vont servir de base solide pour déterminer comment mieux desservir cette population. Pour y arriver, il faudrait considérer le lobbying, l’encouragement des institutions qui dispensent des services de santé d’obtenir leur désignation bilingue, et la mise à jour de la Loi sur les services en français. Cependant, en continuant l’inaction, les Franco-Ontariens risquent de devenir assimilés au restant de la population, de dépérir et de voir leur santé se détériorer. Cet article cherche notamment à signaler la nécessité d’améliorer la prestation de services de santé en français en Ontario.

From Policy to Practice: A Qualitative Study on Reforms and Frontline Retention in Healthcare - Dubé, Anik; Collin, Stéphanie; Hakim, Jennifer; Johnson, Claire; Laforest, Marie-Ève; Landry, Michel H.; Lauzier, Martin (INQUIRY: The Journal of Health Care Organization, Provision, and Financing, 2025)
In Canada, healthcare reforms typically aim to improve the quality of care and access while making healthcare systems more efficient. These reforms have led to a 2-level healthcare system consisting of provincial and regional health authorities (RHAs). RHAs are responsible for providing and administering health services within specific territories. One of the 2 language-based RHAs in New Brunswick (NB) operates in French-speaking rural minority communities. This study explored key factors affecting the retention of nurses and physicians within a RHA operating in a language minority context. This descriptive qualitative study explored how macro-level decisions are experienced on the frontlines. Data were collected through semi-structured interviews with 21 physicians and 37 registered nurses, as well as 2 focus groups involving 20 key informants in managerial roles. Thematic analysis was used to identify key themes. Three main factors emerged: organizational accountability and frustration, local autonomy and contextual responsiveness, and a culture of openness and perceived loss of control. These factors are associated with policy changes that affect operational settings and resource distribution within the RHA and influence the retention of nurses and physicians. Stakeholders in health system reforms, including governments and RHAs, must recognize that policy adjustments can have direct implications on everyday care. Participants expressed a growing disconnect from decision-making hierarchies and a perceived loss of control. Both are seen as barriers to delivering quality care. Ensuring adequate support and resources for implementing system-level changes is key to fostering professional engagement and enhancing job satisfaction.

Multimorbidity: Exploring determinants and differences between Francophones and Anglophones in Ontario - Duong, Patrick; Batista, Ricardo; Lizotte, Mathieu; Sauvé-Schenk, Katrine; Bouchard, Louise (2024)
fs-ref-orig: Duong, P., Batista, R., Lizotte, M., Sauvé-Schenk, K. et Bouchard, L. (2024). Multimorbidity: Exploring determinants and differences between Francophones and Anglophones in Ontario [infographic]. Data User Conference on Health. Ottawa. fs-code-orig: Duong-2024

La multimorbidité : prévalence et déterminants chez les francophones et les anglophones de l’Ontario [affiche] - Duong, Patrick; Lizotte, Mathieu; Batista, Ricardo; Sauvé-Schenk, Katrine; Bouchard, Louise (2025)

L'accessibilité des services sociaux et de santé chez les minorités de langue officielle du Canada et les facteurs influant sur leur accès : une étude de portée - Éthier, Alexandra; Carrier, Annie (Minorités linguistiques et société, 2022)
Les minorités de langue officielle (MLO) du Canada rencontrent des difficultés d’accès aux services sociaux et de santé (SSS). Or, il n’existe aucun portrait exhaustif des services concernés par ces difficultés et des facteurs (facilitateurs et barrières) qui modulent leur accès. Ainsi, le but de cette étude était de décrire l’accessibilité des SSS et d’identifier les facteurs influant sur l’accès aux SSS pour les MLO canadiennes. Une étude de portée dans neuf banques de données combinée à une stratégie élargie a permis d’inclure 74 documents. Les SSS sont généralement insuffisants pour les MLO. De plus, 15 facteurs (8 facilitateurs, 11 barrières) ont été identifiés. Enfin, 26 connexions (une parmi les facilitateurs, 25 parmi les barrières) ont été notées, complexifiant l’accès aux SSS pour les MLO. Intervenir pour favoriser l’accès aux SSS des MLO pourrait être bénéfique à l’ensemble des populations canadiennes, étant donné la présence de barrières communes entre ces groupes. Mots-clés : services sociaux et de santé, minorité anglophone, minorité francophone, facilitateurs, barrières

Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Statistique Canada, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Statistics Canada, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

Analyse des retombées des fonds de recherche du CNFS - Volet université d'Ottawa, période 2013-2020 - Forest, Mariève (Consortium national de formation en santé - Volet Université d'Ottawa, 2020)
fs-ref-orig: Forest, M. (2020). Analyse des retombées des fonds de recherche du CNFS - Volet université d'Ottawa, période 2013-2020. Consortium national de formation en santé - Volet Université d'Ottawa. fs-code-orig: Forest-2020

mobilisation collective pour une santé en français en ontario. closm santé - Forest, Mariève; Gilbert, A.; Bouchard, Louise (Le moment Monfort dans la francophonie canadienne, 2024)

50 ans de législation en matière de langues officielles au Canada : bilan et perspectives - Forgues, Éric; Donovan, Patrick; Labelle Eastaugh, Érik; O’Donnell, Lorraine (Minorités linguistiques et société, 2021)

50 Years of Legislation Concerning Official Languages in Canada: Review and Prospects - Forgues, Éric; Donovan, Patrick; Labelle Eastaugh, Érik; O’Donnell, Lorraine (Minorités linguistiques et société, 2021)

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L’usage de technologies de santé pour accéder à des soins virtuels : une enquête exploratoire pour mieux comprendre les besoins et attentes des francophones de l’Ontario - Grosjean, Sylvie; Giguère, Lauriane; Lessard, Lysanne; Dionne, Émilie (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons les résultats d’une étude visant à répondre à la question suivante : quels usages des technologies numériques de santé sont jugés accessibles et acceptables par les francophones de l’Ontario? Les résultats de cette enquête exploratoire montrent que l’accessibilité et l’acceptabilité des technologies de santé pour soutenir l’offre de soins virtuels chez les francophones de l’Ontario dépendent de plusieurs facteurs liés : a) à leur utilité perçue, b) à leur valeur sociale et leur intégration dans des usages existants, et c) à l’offre des technologies accessibles en français – de leur conception au support offert pour en accompagner les usages. Les résultats de l’étude nous invitent à considérer les questions à la fois communicationnelles (concordance linguistique patient/technologie), organisationnelles (intégration dans des pratiques et structures existantes) et éthiques qu’implique l’usage des technologies de santé visant à soutenir l’offre de soins virtuels pour les francophones de l’Ontario. Mots-clés : soins virtuels, technologies numériques de santé, acceptabilité, francophones, Ontario

Populations de langue officielle en situation minoritaire selon différentes méthodes de dénombrement. Rapport - Guignard Noël, Josée; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2020)

Access to Health and Social Services in Official Languages (Reaffirmation) - Health Standards Organization (2022)
The standard CAN/HSO 11012:2018 (R2022) is a reaffirmation of CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages. The standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. The standard content is grouped into five sections: - Establishing the Active Offer of Services - Clinical Research - Governance and Leadership - Workforce - Quality Assurance
The standard can be bought from this web page.

Accès aux services de santé et aux services sociaux dans les langues officielles (confirmation) - Health Standards Organization / Organisation de normes en santé (2022)
La norme CAN/HSO 11012:2018 (R2022) est une confirmation de la norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles. Elle fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Le contenu de la norme comprend cinq sections : - Établissement de l’offre active de services - Recherche clinique - Gouvernance et leadership - Main-d’oeuvre - Assurance de la qualité
La norme peut être achetée à partir de cette page web.

Language-based welfare services in times of structural change: An examination of Finland’s social and healthcare reform (2023) - Himmelroos, Staffan; Sjöblom, Stefan; Vento, Isak (Revista de Llengua i Dret, 2025)
This study examines the impact of Finland’s social and healthcare reform on language-based welfare services for the Swedish-speaking population of Finland. The reform shifted healthcare responsibility from municipalities to regional wellbeing service counties (WBSCs), altering established linguistic boundaries in the process. Traditionally, municipalities have ensured the provision of services in both Finnish and Swedish in bilingual areas. Post-reform, Swedish speakers that represent a majority or substantial minority within a municipality have become a small minority within larger WBSCs, some of which include unilingual areas that lack experience in providing bilingual services. Analysis of survey data indicates that Swedish speakers in majority Swedish-speaking municipalities are the most satisfied with language services, while those in minority areas are significantly less satisfied. Notwithstanding, satisfaction among Swedish speakers in majority areas has declined significantly since the reform. The study highlights the challenges of maintaining language rights within a universal healthcare system amid structural changes and emphasises the importance of addressing linguistic needs in a state with two national languages. , Aquest estudi analitza l’impacte de la reforma social i sanitària en els serveis socials i de salut basats en la llengua per a la població de parla sueca de Finlàndia. La reforma va traslladar la responsabilitat sanitària dels municipis als serveis regionals de benestar (wellbeing service counties o WBSC), alterant així les fronteres lingüístiques establertes. Tradicionalment, els municipis havien garantit la prestació de serveis tant en finès com en suec a les zones bilingües. Després de la reforma, els parlants de suec que constituïen una majoria o una minoria important dins d’un municipi han passat a ser una petita minoria dins de WBSC més grans, alguns dels quals inclouen àrees unilingües sense experiència en la prestació de serveis bilingües. L’anàlisi de dades provinents d’enquestes indica que els parlants de suec dels municipis de majoria suecoparlant són els més satisfets amb els serveis lingüístics, mentre que els de les àrees on són minoria es mostren significativament menys satisfets. Tanmateix, la satisfacció entre els parlants de suec a les àrees on són majoria ha disminuït notablement des de la reforma. L’estudi destaca els reptes que suposa mantenir els drets lingüístics dins d’un sistema de salut universal enmig de canvis estructurals i posa èmfasi en la importància d’atendre les necessitats lingüístiques en un estat amb dues llengües nacionals. , Este estudio analiza el impacto de la reforma social y sanitaria en los servicios sociales y de salud basados en la lengua para la población de habla sueca de Finlandia. La reforma trasladó la responsabilidad sanitaria de los municipios a los servicios regionales de bienestar (wellbeing service counties o WBSC), alterando así las fronteras lingüísticas establecidas. Tradicionalmente, los municipios habían garantizado la prestación de servicios tanto en finés como en sueco en las zonas bilingües. Después de la reforma, los hablantes de sueco que constituían una mayoría o una minoría importante dentro de un municipio han pasado a ser una pequeña minoría dentro de WBSC mayores, algunos de los cuales incluyen áreas unilingües sin experiencia en la prestación de servicios bilingües. El análisis de datos provenientes de encuestas indica que los hablantes de sueco de los municipios de mayoría suecohablante son los más satisfechos con los servicios lingüísticos, mientras que los de las áreas donde son minoría se muestran significativamente menos satisfechos. Sin embargo, la satisfacción entre los hablantes de sueco en las áreas donde son mayoría ha disminuido notablemente desde la reforma. El estudio destaca los retos que supone mantener los derechos lingüísticos dentro de un sistema de salud universal en medio de cambios estructurales y pone énfasis en la importancia de atender a las necesidades lingüísticas en un estado con dos lenguas nacionales.

Welfare services from a minority perspective. Explaining satisfaction with language-based welfare services among Swedish-speaking Finns - Himmelroos, Staffan; Vento, Isak; von Schoultz, Åsa (Linguistic Minorities and Society, 2021)
fs-ref-orig: Himmelroos, S., Vento, I., & von Schoultz, Å. (2021). Welfare services from a minority perspective. Explaining satisfaction with language-based welfare services among Swedish-speaking Finns. Linguistic Minorities and Society, (15-16), 65-86. https://doi.org/10.7202/1078477ar fs-code-orig: Himmelroos-2021

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Amy. T.; Ménard, Alixe; Scott, Mary (Université d'Ottawa et Institut de recherche Bruyère, 2022)
fs-ref-orig: Hsu, A. T., Ménard, A. et Scott, M. (2022). Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux. Université d'Ottawa et Institut de recherche Bruyère. fs-code-orig: Hsu-2022a

Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Hsu, Amy; Ménard, Alixe; Scott, Mary (Bruyère Research Institut, 2022)
fs-ref-orig: Hsu, A. T., Ménard, A., & Scott, M. (2022). Understanding the long-term care experience of official language minorities in Canada: An environmental scan. Bruyère Research Institut. fs-code-orig: Hsu-2022b

Bilingualism in the health system: The Catalan case - Ibáñez Ferreté, Òscar-Adrià; Mestres i Farré, Neus (Linguistic Minorities and Society, 2021)
Catalan-speaking citizens living in Catalonia have full, formal rights to use their language with all of their region’s administrations. Nevertheless, the available information on the knowledge and use of Catalan by civil servants shows that health care is a weak spot for regional administrations, due to the difficulty in covering all medical specialties. Plataforma per la Llengua has undertaken research in the form of a survey with a sample of 1,600 Catalan inhabitants, to ascertain the level of satisfaction with the enforcement of linguistic rights in public health and determine the scope of a potential language promotion policy that would have health care staff initiate conversations in Catalan. Results of government surveys suggest that language use (by both patients and providers) in the health care system, compared with language use in other areas of public administration, demonstrates the limits of the current regional language promotion policies in Catalonia. Keywords: catalan, linguistic minorities, linguistic rights, health and social services, language competencies

Practice #28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (2025)
fs-ref-orig: Ibrahim, N., Benoît, J. & Savard, J. (2025). Practice 28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario). In: GReFoPS. Directory of Innovative Practices in Health and Social Services in Official Language Minority Contexts. https://www.grefops.ca/directory_ innovative_practices.html fs-code-orig: Ibrahim-2025

La mobilisation des connaissances en santé dans les petites communautés francophones en situation minoritaire. Ses défis, ses conditions de succès - Johnson, Marc. L.; Cimon, Virginie; Dancause, Luc; Forest, Mariève (SOCIUS recherche et conseils, 2021)

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

Recueil des outils proposés dans le guide pratique Plaidoyer pour la santé - Knaidil, Ibtissam; Chaput, Sarah (Réseau francophone international pour la promotion de la santé, 2022)

Tensions linguistiques au Nouveau-Brunswick : attitudes à l’égard du bilinguisme dans le système de santé. - Landry, Michelle; Legault-Leclair, Jacob; McLaughlin, Gilbert (Minorités linguistiques et société, 2024)
Dans cet article, nous examinons les opinions des anglophones à l’égard du bilinguisme dans le système de santé. Les données proviennent d’un sondage mené par la firme Léger du 16 au 24 février 2021. Nous avons mesuré l’effet d’une série de variables sociodémographiques, de l’orientation politique et de l’accord avec un énoncé selon lequel les francophones constitueraient un groupe privilégié sur le fait d’être d’avis que les services bilingues sont suffisamment développés dans le secteur de la santé. En conclusion, les résultats indiquent que les électeurs des partis politiques conservateurs et du People’s Alliance ont en majorité tendance à estimer que le bilinguisme en santé est suffisamment développé. Les variables sociodémographiques et le fait d’affirmer que les francophones représentent un groupe privilégié ne sont pas des variables discriminantes dans notre analyse. Mots-clés : Bilinguisme, Nouveau-Brunswick, système de santé, Acadie, services en français

Loi sur les langues officielles et vitalité des minorités : mission impossible ou oeuvre inachevée ? - Landry, Rodrigue (Minorités linguistiques et société, 2021)
Notre article vise à déterminer les conditions nécessaires pour qu’une loi et des politiques linguistiques puissent avoir un effet réel sur la vitalité d’une minorité. L’article comprend trois parties. Premièrement, nous concluons que la Loi sur les langues officielles (LLO) a eu peu d’effet sur la vitalité des minorités de langue officielle. En deuxième partie, nous distinguons trois acteurs essentiels qui agissent sur la vitalité linguistique : la communauté d’intimité, la société civile de la minorité et l’État. De ces analyses, nous dégageons deux principes sociolinguistiques que toute législation linguistique devrait respecter si son objet est de favoriser la vitalité/revitalisation d’une minorité. Enfin, nous focalisons sur la partie VII de la LLO, la plus susceptible de favoriser la mise en oeuvre d’un aménagement linguistique planifié et global capable de respecter les deux principes sociolinguistiques, de coordonner une synergie d’action des acteurs essentiels et d’avoir un effet réel sur la vitalité des minorités. Mots-clés : Loi sur les langues officielles, vitalité ethnolinguistique, autonomie culturelle, aménagement linguistique, politiques linguistiques, droits linguistiques

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final - Léger (Santé Canada, 2020)
fs-ref-orig: Léger. (2020). Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final. Santé Canada. fs-code-orig: Léger-2020

Operationalising linguistic unease for the evaluation of language policies in healthcare - Marinaro, Nicole (Revista de Llengua i Dret, 2025)
This contribution presents an original methodological tool for the systematic evaluation of the relevance and comprehensiveness of healthcare language policy design. In particular, the focus of the analysis are public policies that address communication barriers experienced by patients who speak autochthonous or allochthonous languages other than the majority language in their interaction with the healthcare system. Such communication barriers are here conceptualised as “linguistic unease”. Within the epistemological framework of public policy analysis, the tool presented in the article hinges on the operationalisation of the concept of linguistic unease and is hence built on the centrality of the consideration of speakers’ needs. After outlining instances of linguistic unease in healthcare, the article presents the tool in detail and illustrates its employment through a brief practical example. , Aquest article presenta una eina metodològica original per a l’avaluació sistemàtica de la rellevància i l’exhaustivitat del disseny de polítiques lingüístiques en l’atenció sanitària. En concret, l’anàlisi se centra en les polítiques públiques que aborden les barreres de comunicació que experimenten els pacients que parlen llengües autòctones o al·lòctones diferents de la llengua majoritària a l’hora d’interactuar amb el sistema de salut. Aquestes barreres comunicatives es conceptualitzen com a “incomoditat lingüística”. Dins del marc epistemològic de l’anàlisi de les polítiques públiques, l’eina presentada a l’article es basa en l’operacionalització del concepte d’incomoditat lingüística i, com a tal, s’articula al voltant de la centralitat de les necessitats dels parlants. Després d’exposar diversos casos d’incomoditat lingüística en l’atenció sanitària, l’article descriu l’eina en detall i n’il·lustra l’ús a través d’un breu exemple pràctic. , Este artículo presenta una herramienta metodológica original para la evaluación sistemática de la relevancia y la exhaustividad del diseño de políticas lingüísticas en la atención sanitaria. En concreto, el análisis se centra en las políticas públicas que abordan las barreras de comunicación que experimentan los pacientes que hablan lenguas autóctonas o alóctonas diferentes de la lengua mayoritaria en sus interacciones con el sistema de salud. Estas barreras comunicativas se conceptualizan como “incomodidad lingüística”. Dentro del marco epistemológico del análisis de las políticas públicas, la herramienta presentada en el artículo se basa en la operacionalización del concepto de “incomodidad lingüística” y, como tal, se articula en torno a la centralidad de las necesidades de los hablantes. Después de exponer varios casos de incomodidad lingüística en la atención sanitaria, el artículo describe la herramienta en detalle e ilustra su uso a través de un breve ejemplo práctico.

Validation culturelle d’un outil numérique francophone pour l’histoire médicale en soins de santé primaires - McGraw, Monica; Dionne Merlin, Marjolaine; Dion, Cynthia; Renaud, Julie; Légère, Danika; Poirier, Marie-Dominique (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
La technologie de santé numérique s’intègre dans les soins de santé améliorant l’engagement des patients dans les décisions partagées, favorisant ainsi leur prise en charge et la qualité des soins. FirstHx développe des outils innovants dans cette optique, mais leur mise en oeuvre est complexe pour la population francophone dans un contexte majoritairement anglophone. Cette étude vise à valider culturellement cet outil et à évaluer la satisfaction des utilisateurs. Une méthodologie mixte séquentielle explicative est employée en trois phases : un sondage quantitatif pour tester la clarté des questions, des entretiens semi-dirigés pour explorer la traduction culturelle et la convivialité, et une validation par des experts via la méthode Delphi. L’outil validé optimisera les pratiques cliniques, normalisera la saisie des données d’anamnèse et ouvrira de nouvelles perspectives de recherche. Cette validation offrira à la population francophone un accès équitable à des outils numériques innovants, renforçant leur engagement dans leurs soins. Digital health technology is being integrated into healthcare, improving patient engagement in shared decision-making, thereby promoting their care and the quality of care. FirstHx develops innovative tools with this goal in mind, but their implementation is complex for the Francophone population in a predominantly English-speaking context. This study aims to culturally validate this tool and assess user satisfaction. A sequential explanatory mixed-method approach is used in three phases: a quantitative survey to test question clarity, semi-structured interviews to explore cultural translation and user-friendliness, and validation by experts using the Delphi method. The validated tool will optimize clinical practices, standardize the collection of medical history data, and open new research opportunities. This validation will provide the Francophone population with equitable access to innovative digital tools, strengthening their engagement in their healthcare.

Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Ménard, Alixe; Scott, Mary; Hsu, Amy T. (2022)
fs-ref-orig: Ménard, A., Scott, M. et Hsu, A. T. (2022). Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan. Institut de recherche Bruyère. fs-code-orig: Ménard-2022

The Basque paradigm shift: From legislative language policies to person-centred care - Montes Lasarte, Aitor; Arauzo, Xabier; Zarate Sesma, Jon (Linguistic Minorities and Society, 2021)
The Basque Country has two official languages, Basque and Spanish, the first being spoken by 37% of the population. The Basque Health Service has developed language schemes to fulfill the legal requirements. Currently, there is a vast transformational shift from legislative policies to an evidence-based, patient-centred care approach. This paper discusses three key issues which could enhance language appropriate care: the recording of patient’s preferred language; the Basque language care pathways as a suitable and effective approach for determining the language of service along the continuum of care; and bilingual electronic medical records, which bring to the fore the challenge of language barriers among professionals. Considering its bilingual human resources, it offers an opportunity for establishing compelling evidence about implementation. Keywords: patient-centred care, bilingual pathways, language appropriate care, preferred language, active offer

Official Language Minority Communities in Ontario: Understanding the Lived Experiences of Francophone Patients and their Nursing Care Providers - Muray, Mwali (2022)
Although Canada is a bilingual country, official language minority community patients struggle to access quality care in their language. This reality has been of concern for Francophone minority communities in Ontario, but has seldom been examined in a nursing context. This research sought to examine the lived experiences of registered nurses and nursing students providing care to French-speaking patients in Ontario, as well as the realities of Francophone patients seeking French language health care services in Ontario. The conceptual frameworks guiding the study were the “Four Levels of Change for Improving Quality” model and the “Four-Level Model of the Health Care System.” Using qualitative phenomenological inquiry, as influenced by Martin Heidegger and Max van Manen, 31 semi-structured interviews were conducted with three subsets (n=10 Francophone patients; n=10 nursing students; n=11 registered nurses) throughout Ontario who had experience with the phenomenon being investigated. Data collection took place over a year (2018-2019) and was analysed thematically. Significant findings were identified across the three groups. Participants revealed the patchwork of individual actions taking place to remedy the existing gaps regarding care for Francophone minority populations. This included navigating a health care system where good enough care was the unfortunate standard for Francophone patients, and discussing how Francophone patients and nursing care providers implement strategies individually to manage the lack of resources for Francophone patient populations in Ontario. This thesis asserts that official language minority communities and their nursing care providers remain faced with difficulties providing and receiving care in Ontario. While numerous structures and resources exist to remediate the problems, these interventions and resources are not always implemented systemically, leading to a disproportionate burden on individuals, significant risks for safety for patient populations, and ethical dilemmas for nursing care providers. Recommendations are provided to bridge the gaps and ensure considerations of the needs of linguistic minorities throughout the health care system. Keywords: Francophonie, Linguistic Minorities, Nursing, Phenomenology, Qualitative Research

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

The revised patient perception of patient-centeredness questionnaire: Exploring the factor structure in French-speaking patients with multimorbidity - Nguyen, Tu Ngoc; Ngangue, Patrice Alain; Ryan, Bridget. L.; Stewart, Moira; Brown, Judith. B.; Bouhali, Tarek; Fortin, Martin (Health Expectations, 2020)
Background The Patient Perception of Patient-Centeredness (PPPC) questionnaire was revised, and there is a need for the questionnaire to be tested in diverse primary care populations. Objectives This study aimed to examine the factor structure of the Revised PPPC questionnaire (PPPC-R) in French-speaking patients with multimorbidity. Design Secondary analysis from baseline data of the French arm of Patient-Centered Innovations for Persons with Multimorbidity Study (PACEinMM Study). Setting and participants Participants were adult patients with multimorbidity attending primary health-care settings. Outcome measures Exploratory factor analyses were applied to examine the factor structure of the PPPC-R. Cronbach's alpha values were calculated to assess the internal consistency of the whole questionnaire and of each factor explored. Results There were 301 participants, mean age 61.0, 53.2% female. The PPPC-R showed very good internal consistency, with three factors: Patient-Centered Clinical Method (PCCM) Component 1-Exploring the health, disease and illness experience + PCCM Component 4-Enhancing the patient–clinician relationship (Factor 1); PCCM Component 2-Understanding the whole person (Factor 2); and PCCM Component 3-Finding common ground (Factor 3). There was a good internal consistency within each factor (Cronbach's α = 0.87 for 8 items in Factor 1, 0.77 for 5 items in Factor 2 and 0.87 for 5 items in Factor 3). Discussion and conclusions The French PPPC-R factor structure was in accordance with the underpinning conceptual model and presented with three factors. Further assessment of its validity and reproducibility are needed to allow its use as a measure of patient's perception of patient-centeredness.

The new Inclusive definition of Francophone (IDF) - Office of Francophone Affairs (2020)

Problèmes d’accès aux services en français ? Contactez-nous. Nous pouvons vous aider [infographie] - Ombudsman de l'Ontario (2022)

Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication] - Ontario mental health & addictions virtual care collaborative (Centre for Addiction and Mental Health (CAMH), 2021)
fs-ref-orig: Ontario mental health & addictions virtual care collaborative. (2021). Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication]. Centre for Addiction and Mental Health (CAMH). fs-code-orig: Ontario mental health & addictions virtual care collaborative-2021

Problems accessing services in French? Contact us. We can help [infographie] - Ontario Ombudsman (2022)

Connaissance et utilisation de la langue officielle minoritaire au travail par les travailleurs de la santé, 2001 à 2016 - Paez Silva, Alejandro. A.; Cornelissen, Louis (Statistique Canada, 2021)

Knowledge and use of the Official Minority Language at work by healthcare workers, 2001 to 2016 - Paez Silva, Alejandro. A.; Cornelissen, Louis (Statistics Canada, 2021)

Francophone patients - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

Patientèle francophone - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

Situation des populations de langue anglaise au Québec et de langue française au Canada hors Québec : résultats de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
Le présent rapport et l’Enquête sur la population de langue officielle en situation minoritaire de 2022 ont bénéficié du soutien financier et de la collaboration soutenue du ministère du Patrimoine canadien. Cette étude a pu être réalisée grâce au travail de longue haleine de plusieurs équipes et personnes qui se sont relayées au fil des ans pour planifier, concevoir, préparer, tester, réaliser, assurer la qualité des données, documenter, analyser et diffuser cette enquête d’envergure. Les auteurs tiennent à remercier toutes les personnes qui ont participé à ce processus, en particulier, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑ Hélène Toupin, Danielle Léger et Catherine Dufour. Plusieurs autres membres du personnel actuel ou passé de Statistique Canada ont contribué de manière importante à cette enquête au fil du temps, dont Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean‑Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu et Dominique Pérusse, de même que les équipes internes des activités de collecte et de traitement des données. Pour leur soutien, leurs conseils et leur aide à la production du rapport, merci à Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini et Pierre‑France Bondesen‑David. Soulignons également l’expertise et l’orientation fournies par les réviseurs ainsi que les membres du comité de direction et les membres du comité scientifique de l’enquête.

Situation of English-speaking populations in Quebec and French-speaking populations in Canada outside Quebec: Results of the 2022 Survey on the Official Language Minority Population - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
This report and the 2022 Survey on the Official Language Minority Population received funding and ongoing support from the Department of Canadian Heritage. This study was made possible thanks to the tireless efforts of many different teams and individuals who, over the years, contributed to planning, designing, preparing, testing, conducting, ensuring data quality, documenting, analyzing and publishing this major survey. The authors would like to thank each and every one of them, especially, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑Hélène Toupin, Danielle Léger and Catherine Dufour. Many other current or former Statistics Canada staff members have made, over the years, important contributions to this survey including Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu and Dominique Pérusse, as well as the in‑house data collection and processing teams. For their support, advice and help in producing the report, thanks to Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini and Pierre‑France Bondesen‑David. We would also like to acknowledge the expertise and guidance of the editors, as well as the members of the Interdepartmental Steering Committee and the survey Scientific Committee.

Approach to the status and management of languages in the catalan public health care system - Pere Mas, Jordi (Linguistic Minorities and Society, 2021)
This article deals with the situation of languages in healthcare in Catalonia. It reports on the measures being carried out by the Ministry of Health of the Government of Catalonia to guarantee that the population may be attended to in their own official language, whether Catalan, Spanish or Occitan, and specifically to promote knowledge and use of Catalan among professionals working in the health system. It provides data on the migratory flows of doctors and nurses and sociolinguistic data. Other sections deal with healthcare services provided in non-official languages and in Catalan sign language, as well as language-related complaints and the measures implemented to make Catalan a suitable and prestigious language for medical and scientific communication. It concludes by listing the challenges that still need to be tackled to give Catalan greater presence and to raise its status in the field of health. Keywords: healthcare, health, Catalan, linguistic planning, healthcare professionals, official languages, Catalonia

Quebec’s English-speaking community and the partnership approach of its networks in health - Pocock, Joanne (Linguistic Minorities and Society, 2021)
This article discusses the networking and partnership approach of improving access to public health and social services, with an interest in informing best practices for official language populations in a minority context. The case of Canada’s official language minority residing in the province of Quebec and its Community Health and Social Services Network (CHSSN) is explored. Elements that support or inhibit partnership functioning, including innovative community-based participatory evaluation (CBPE) techniques, are explored. The contribution of the approach in improving the situation of Quebec’s minority language communities with respect to their health care access is highlighted. Keywords: official language minority communities, intersectoral partnerships, access to public health care, language policy, community-based participatory evaluation (CBPE)

Substance Use, Addiction and Support Services: Increased Risk and Service Inequity for Official Language Minority Communities in Canada - Prada, Kevin; de Moissac, Danielle (The Canadian Journal of Addiction, 2024)
Abstract Objectives: The increase in substance use and addictions within the Canadian population, illustrated by the current opioid crisis and exacerbated by the COVID-19 pandemic, urges the investigation of populations who may be particularly vulnerable to developing problematic substance use. Official language minority communities in Canada, both understudied and underserved, may be one such population. Methods: Through its tripartite design using scoping literature review, interview, and environmental scan methodologies, this study offers a snapshot of the current reality surrounding substance use, addictions, and related treatment services available to this linguistic minority population. Results: Results reveal significant gaps in knowledge and service provision for this population. Service provision and knowledge on this issue constitute a nationwide patchwork, leaving official language minority communities underserved. While enough is known to assert that their needs are different than those of their majority peers, much remains to be investigated, and efforts to ameliorate their social determinants of health, including cultural and linguistic competence on behalf of service providers, are urgently needed. Conclusions: Recommendations include networking, collaboration, financial support and active offer of services in both official languages to improve mental health and addictions services through a continuum of care. Systems navigators may facilitate promotion and referral to such services for official language minorities. Résumé Objectifs: La prévalence croissante de la consommation des substances et des dépendances au Canada, tel qu’illustrée par la crise actuelle des opioïdes et exacerbée par la pandémie de la COVID-19, exhorte à l’investigation de populations qui pourraient être particulièrement vulnérables à la consommation problématique de substances. Au Canada, les communautés de langue officielle en situation de minorité (CLOSM), une population à la fois peu étudiée et peu desservie, pourrait bien représenter une telle population. Méthodes: Au moyen de sa stratégie tripartite, employant les méthodologies d’étude de la portée, d’entrevues, et de scan environnemental, cette étude brosse un premier portrait de la réalité actuelle quant à la consommation de substances, aux dépendances et aux services qui y sont voués, parmi les CLOSM au Canada. Résultats: Les résultats révèlent une lacune importante aux niveaux des connaissances et des services desservant les CLOSM dans la majorité des provinces et territoires. Bien que l’état des lieux soit parcellaire en raison du manque d’études scientifiques sur la question, le portrait actuel suffit pour constater que les besoins des CLOSM différent de ceux de leurs pairs de langue majoritaire. Une amélioration des déterminants sociaux de la santé, tel la compétence culturelle et linguistique de la part des pourvoyeurs des services, représente un besoin pressant. Conclusions: Les recommandations, qui comprennent le réseautage, la collaboration, l’appui financier et l’offre active des services dans les deux langues officielles, visent à améliorer les services voués à la santé mentale et aux dépendances auprès des CLOSM au sein d’un continuum de soins. Les navigateurs.rices de systèmes pourraient faciliter l’aiguillage de membres des CLOSM vers ces services.

Navigating the meso-level bottleneck: Language rights implementation in Welsh healthcare - Prys, Cynog; Hodges, Rhian (Revista de Llengua i Dret, 2025)
Language is a key factor in the delivery of effective healthcare, especially in settings where service users speak a minoritised language. In Wales, the Welsh Government has acknowledged the importance of linguistic inclusion through initiatives such as the More than just words strategy, which aims to embed the Welsh language into health and social care services. The introduction of The Welsh Language Standards (No. 7) Regulations in 2018 marked a significant statutory development, placing legal obligations on health boards to provide services in Welsh. Despite these policy-level advancements, the integration of Welsh language services within healthcare remains uneven. Reports have highlighted persistent gaps and inconsistencies in Welsh language service provision, raising concerns about the practical challenges of implementation and its impact on service users. In this paper, we examine the structural and operational barriers encountered by meso-level actors – particularly local health boards – responsible for implementing national language policy in everyday service delivery. Although the analysis is situated in the Welsh context, the paper contributes to a broader understanding of the administrative bottlenecks that can arise when implementing public services in a minoritised language context. It highlights the need to critically examine the institutional dynamics that shape the translation of policy into practice and the implications for minoritised languages such as Welsh. , La llengua és un element clau en la prestació d’una atenció sanitària de qualitat, sobretot en contextos en què els usuaris parlen una llengua minoritzada. A Gal·les, el Govern gal·lès ha reconegut la importància de la inclusió lingüística a través d’iniciatives com ara l’estratègia More than just words, que té l’objectiu d’integrar la llengua gal·lesa als serveis de salut i d’assistència social. L’any 2018, la introducció del Reglament núm. 7 sobre la llengua gal·lesa va marcar un avenç normatiu important, ja que va imposar obligacions legals d’oferir serveis en gal·lès als consells de salut. Malgrat aquests avenços a nivell polític, la incorporació de serveis en llengua gal·lesa en l’atenció sanitària continua sent desigual. Alguns informes han posat de manifest l’existència de buits continuats i d’incoherències en la prestació de serveis en gal·lès, cosa que ha suscitat interrogants sobre els reptes pràctics de la seva implementació i l’impacte que té en els usuaris. En aquest article s’analitzen les barreres estructurals i operatives que es troben els agents situats al nivell meso –en concret els consells de salut locals– responsables d’implementar les polítiques lingüístiques nacionals en l’atenció diària. Malgrat que l’anàlisi se situa en el context gal·lès, l’article aporta una visió més àmplia dels colls d’ampolla administratius que poden sorgir a l’hora d’implementar serveis públics en un context de llengües minoritzades. També destaca la necessitat d’analitzar críticament les dinàmiques institucionals que modulen la traducció de les polítiques a la pràctica i les implicacions per a llengües minoritzades com ara el gal·lès. , La lengua es un elemento clave en la prestación de una atención sanitaria de calidad, sobre todo en contextos en que los usuarios hablan una lengua minorizada. En Gales, el Gobierno galés ha reconocido la importancia de la inclusión lingüística a través de iniciativas como la estrategia More than just words, que tiene el objetivo de integrar la lengua galesa en los servicios de salud y de asistencia social. En 2018, la introducción del Reglamento núm. 7 sobre la lengua galesa marcó un avance normativo importante, ya que impuso obligaciones legales de ofrecer servicios en galés en los consejos de salud. A pesar de estos avances a nivel político, la incorporación de servicios en lengua galesa en la atención sanitaria sigue siendo desigual. Algunos informes han puesto de manifiesto la existencia de vacíos continuados e incoherencias en la prestación de servicios en galés, lo que ha suscitado interrogantes sobre los retos prácticos de su implementación y el impacto que tiene en los usuarios. En este artículo se analizan las barreras estructurales y operativas que encuentran los agentes situados al nivel meso –en concreto los consejos de salud locales– responsables de implementar las políticas lingüísticas nacionales en la atención diaria. Aunque el análisis se sitúa en el contexto galés, el artículo aporta una visión más amplia de los cuellos de botella administrativos que pueden surgir a la hora de implementar servicios públicos en un contexto de lenguas minorizadas. También destaca la necesidad de analizar críticamente las dinámicas institucionales que modulan la traducción de las políticas a la práctica y las implicaciones para lenguas minorizadas como el galés.

Rhetoric and reality: A critical review of language policy and legislation governing official minority language use in health and social care in Wales - Prys, Cynog; Hodges, Rhian; Roberts, Gwerfyl Wyn (Linguistic Minorities and Society, 2021)
A concerted attempt is being made by the Welsh Government to revitalize the Welsh language in Wales through language legislation and policy initiatives. This paper explores the political rhetoric and practical reality of these recent legislative developments, as they pertain to the health care sector. It offers a qualitative analysis of written evidence provided by key stakeholders during the consultation process on the new legally-binding requirements of Welsh Language Standards for health care providers in Wales. We argue that these meso-level service providers are critical linchpins within the health care system and that it is at the meso level that full tensions between the macro rhetoric and micro reality occur. This contribution highlights shortcomings and barriers to Welsh language service provision in health care in Wales and recommends the adoption of wide-ranging, holistic approaches to language planning that meet the language needs of patients outlined by the Welsh Government. Keywords: health and social care, language planning, minority language, Welsh, Wales

The impact of language on emergency department visits, hospitalizations, and lenght of stay among home care recipients - Reaume, M.; Batista, Ricardo; Rhodes, Emily; Knight, Braden; Imsirovic, Haris; Seale, Emily; Riad, Karine; Prud'homme, Denis; Tanuseputro, Peter (Medical care, 2021)
Background: Research considering the impact of language on health care utilization is limited. We conducted a population-based study to: (1) investigate the association between residents’ preferred language and hospital-based health care utilization; and (2) determine whether this association is modified by dementia, a condition which can exacerbate communication barriers. Methods: We used administrative databases to establish a retrospective cohort study of home care recipients (2015–2017) in Ontario, Canada, where the predominant language is English. Residents’ preferred language (obtained from in-person home care assessments) was coded as English (Anglophones), French (Francophones), or other (Allophones). Diagnoses of dementia were ascertained with a previously validated algorithm. We identified all emergency department (ED) visits and hospitalizations within 1 year. Results: Compared with Anglophones, Allophones had lower annual rates of ED visits (1.3 vs. 1.8; P<0.01) and hospitalizations (0.6 vs. 0.7; P<0.01), while Francophones had longer hospital stays (9.1 vs. 7.6 d per admission; P<0.01). After adjusting for potential confounders, Francophones and Allophones were less likely to visit the ED or be hospitalized than Anglophones. We found evidence of synergism between language and dementia; the average length of stay for Francophones with dementia was 25% (95% confidence interval: 1.10–1.39) longer when compared with Anglophones without dementia. Conclusions: Residents whose preferred language was not English were less frequent users of hospital-based health care services, a finding that is likely attributable to cultural factors. Francophones with dementia experienced the longest stays in hospital. This may be related to the geographic distribution of Francophones (predominantly in rural areas) or to suboptimal patient-provider communication.

Qualité et sécurité des services de santé offerts en situation linguistique minoritaire en Ontario : investigations des données administratives de santé. - Reaume, Michael; Batista, Ricardo; Prud’homme, Denis; Tanuseputro, Peter (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons une synthèse de plusieurs analyses récentes réalisées par notre groupe de recherche à partir de données administratives de santé pour mesurer la qualité et la sécurité des services de santé offerts aux francophones et allophones en Ontario, Canada. Les résultats de nos analyses démontrent que les Ontariennes et les Ontariens qui reçoivent des soins dans leur principale langue d’usage ont généralement de meilleurs résultats cliniques comparés à ceux qui reçoivent des soins dans une langue autre que leur principale langue d’usage. Ceci suggère que la qualité et la sécurité des soins offerts aux patients et aux patientes en situation de discordance linguistique pourraient être améliorées par le pairage de professionnel-patient parlant la même langue, par exemple, en référant un patient à un médecin qui parle la langue du patient, ou en s’assurant que les francophones ont accès aux services en français en milieux désignés en Ontario en vertu de la Loi sur les services en français et que les allophones puissent bénéficier de davantage de services d’interprétariat. Mots-clés : allophones, données administratives de santé, francophones, minorités de langue officielle, minorités linguistiques, qualité et sécurité des soins de santé

In-hospital patient harm across linguistic groups: A retrospective cohort study of home care recipients - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Guerin, Eva; Rhodes, Emily; Carson, Sarah; Prud'homme, Denis; Tanuseputro, Peter (Journal of patient safety, 2022)
Objective Research examining the impact of language barriers on patient safety is limited. We conducted a population-based study to determine whether patients whose primary language is not English are more likely to experience harm when admitted to hospitals in Ontario, Canada. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2010 to 2015) who were subsequently admitted to hospital. Patient language (obtained from home care assessments) was coded as English, French, or other. Harmful events were identified using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results We included 190,724 patients (156,186 Anglophones, 5,110 Francophones, and 29,428 Allophones). There was no significant difference in the unadjusted risk of harm for Francophones compared with Anglophones (relative risk [RR], 0.94; 95% confidence interval [CI], 0.87–1.02). However, Allophones were more likely to experience harm when compared with Anglophones (RR, 1.14; 95% CI, 1.10–1.18). The risk of harm was even greater for Allophones with low English proficiency (RR, 1.18; 95% CI, 1.13–1.24). After adjusting for potential confounders, Anglophones and Allophones were equally likely to experience harm of any type, but Allophones more likely to experience harm from infections and procedures. Conclusions Patients whose primary language was not English or French were more likely to experience harm after admission to hospital, especially if they had low English proficiency. For these patients, the risk of harm from infections and procedures persisted in the adjusted analysis, but the overall risk of harm did not.

Patient-Physician Language Concordance and Cardiovascular Outcomes Among Patients With Hypertension. - Reaume, Michael; Labossière, Mathieu N.; Batista, Ricardo; Van Haute, Stephanie; Tangri, Navdeep; Rigatto, Claudio; Bohm, Clara; Prud’homme, Denis; Tanuseputro, Peter; Lix, L. M. (JAMA Network Open, 2025)
Importance Patients who live in minority language communities often receive health care services of lower quality and safety compared with patients who speak the majority language. Yet the outcomes associated with care provided by physicians who speak a patient’s primary language remain unknown. Objective To examine patient-physician language concordance and the risk of major adverse cardiovascular events (MACEs) among patients with hypertension. Design, Setting, and Participants This retrospective cohort study identified adults with self-reported hypertension in the Canadian Community Health Survey, a national survey that collects data from a representative sample of Canadians, from January 1, 2003, to December 31, 2014. Respondents (excluding those living in Quebec) had their hospitalization and mortality records linked to their survey responses. Data were analyzed from October 2023 to May 2024. Exposures Respondents’ primary home language was defined using language spoken most often at home. Language spoken with a regular physician was used to measure patient-physician language concordance. Respondents who spoke to their regular physician in their primary home language were classified as having received language-concordant care, while all other respondents were classified as having received language-discordant care.

La population francophone au sein de votre équipe Santé Ontario : proposition d’indicateurs clés - Réseau des services de santé en français de l'Est de l'Ontario (2022)
fs-ref-orig: Réseau des services de santé en français de l'Est de l'Ontario. (2022). La population francophone au sein de votre équipe Santé Ontario : proposition d’indicateurs clés [infographie]. fs-code-orig: Réseau des services de santé en français de l'Est de l'Ontario-2022a (PDF à séparer)

Le Réseau à l’écoute. Rapport à la communauté 2022-2023. - Réseau des services de santé en français de l’Est de l’Ontario (2024)

Le Réseau à l’écoute. Rapport à la communauté 2023-2024. - Réseau des services de santé en français de l’Est de l’Ontario (2024)

Mémoire sur la santé numérique en français en Ontario. Examen des documents d'orientation stratégique - Réseau des services de santé en français de l'Est de l'Ontario (2021)

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Final Report – Improving the Francophone Experience in Healthcare - Réseau du mieux-être francophone du Nord de l'Ontario (2021)

Rapport final – Amélioration de l’expérience des francophones dans les soins de santé - Réseau du mieux-être francophone du Nord de l'Ontario (2021)

À la rencontre des communautés acadiennes et francophones et de leurs enjeux en santé - Réseau Santé (Réseau santé en français de Nouvelle-Écosse, 2021)

Argumentaire pour la promotion d’une offre de service santé de qualité dans la langue maternelle des clients au Nunavut - Réseau Santé en français au Nunavut (2021)

Améliorer l’état de santé des francophones de Terre Neuve-et-Labrador - Réseau Santé en français de Terre-Neuve-et-Labrador (2021)

Santé des francophones en milieu minoritaire. Quelle est la situation en Colombie-Britannique ? | The health of Francophone minorities. What does it mean for British Colombia? - RésoSanté Colombie-Britannique (What does it mean for British Colombia, 2021)

Report on the 2020–2023 Café de Paris Manitoba Pilot Project - Roberge, Jérémie (Santé en français Manitoba, 2023)

5 enjeux prioritaires en santé des communautés acadienne et francophones - Santé Nouvelle-Écosse; Réseau Santé Nouvelle-Écosse (2022)

Données sur les soins de longue durée en français-Équipe Santé Ontario du Grand Fleuve - Santé Ontario; Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada (2022)
fs-ref-orig: Santé Ontario, Réseau des services de santé en français de l'Est de l'Ontario et Santé Canada. (2022). Données sur les soins de longue durée en français : équipe Santé Ontario du Grand Fleuve [infographie]. fs-code-orig: Santé Ontario-2022a

Évaluation de la mise en œuvre de services en français en contexte minoritaire : développement d’un questionnaire sur l’expérience des usagers - Sauvé-Schenk, K; Savard, Jacinthe; Savard, Sébastien; Prud’homme, Denis; van Kemenade, Solange; Le Callonnec, L; Pignac, S (2022)

Challenges faced by bilingual stroke survivors in the healthcare system: Unique considerations - Sauvé-Schenk, Katrine; Dubouloz-Wilner, Claire-Jehanne; Egan, Mary; Kristjansson, Elizabeth (Linguistic Minorities and Society, 2020)
The experiences of multilingual patients communicating with unilingual healthcare providers have been largely unexplored. The aim of this study was to investigate the experiences of bilingual stroke patients within the Canadian healthcare context. A secondary analysis was completed with data from a multiple case study of the experiences of seven, low-income bilingual Francophone stroke survivors living in a predominately English area. Data included semi-structured interviews, chart reviews and language proficiency assessments. Results demonstrated that bilingual survivors experience unique challenges, including limited French health vocabulary, use of non-standard French, and generally low health literacy levels in both languages. Participants with aphasia often used English and French interchangeably, leading to the potential for miscommunication when providers were not bilingual. The study highlights the importance of having bilingual healthcare providers when bilingual stroke survivors have communication or cognitive limitations. Keywords: Stroke, language, bilingualism, healthcare, literacy

L’expérience des francophones des soins et des services en contexte linguistique minoritaire : bilan et perspectives. - Sauvé-Schenk, Katrine; Savard, Jacinthe; Miljours, Jean-Christophe; Bouchard, Louise (Minorités linguistiques et société, 2024)
L’objectif de cet article est de présenter un état des lieux de la recherche qui porte sur l’expérience des bénéficiaires de services sociaux et de santé en contexte francophone minoritaire. On y traite des perceptions envers les services sociaux et de santé, de la demande de services en français ainsi que des expériences d’accès à des services en français, des barrières linguistiques et de la navigation dans le système de santé. On y traite aussi les perspectives qu’apportent les recherches en cours pour 1) mieux saisir les perceptions des francophones à l’égard de l’utilisation des technologies en santé afin d’améliorer leur accès aux services en français et 2) intégrer la mesure de la perception des usagers à l’évaluation continue des services en français. Mots-clés : expérience patient, minorité linguistique, francophone, système de santé, Canada

Conditions gagnantes pour une offre active de services en français efficace dans un milieu à faible densité de francophones : résultats d’une étude pilote. Rapport sommaire présenté à la Société Santé en français - Sauvé-Schenk, Katrine; Savard, Jacinthe; Prud’homme, Denis; Durand (Chiocchio), F.; Delluc, C. (Institut du savoir Montfort et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)
fs-ref-orig: Sauvé-Schenk, K., Savard, J., Prud’homme, D., Durand (Chiocchio), F. et Delluc, C. (2021). Conditions gagnantes pour une offre active de services en français efficace dans un milieu à faible densité de francophones : résultats d’une étude pilote. Rapport sommaire présenté à la Société Santé en français. Institut du savoir Montfort et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire. fs-code-orig: Sauvé-Schenk-2021

Pratique # 6 : Café de Paris (Nouveau-Brunswick) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

A self-assessment tool for healthcare and social service provision in French: What use for managers? - Savard, Sébastien; Savard, Jacinthe; van Kemenade, Solange; Benoît, Josée; Tabor, Michelle (Healthcare Management Forum, 2020)
Language is an important determinant of health, and lack of access to quality, linguistically adapted healthcare and social services negatively impacts users. Besides the lack of bilingual resources, our previous research on Francophone minority community seniors’ trajectories through these services shed light on important and nonobvious challenges currently faced by organizations offering healthcare and social services to this population. Current service provision appeared limited due to organizations working in silos with suboptimally used resources for integrating active offer of French language services throughout the continuum of care. This situation led our team to create the Organizational and Community Resources Self-Assessment Tool for Active Offer and Continuity of French Language Healthcare and Social Services, which is intended to help managers and service providers promote and facilitate the integration of active offer throughout the continuum of service provision. This article describes the Tool’s creation, content validation, and pilot-testing.

Vers de nouvelles approches en santé mentale : possibilités et limites pour les francophones en situation minoritaire à Terre-Neuve-et-Labrador et aux Territoires du Nord-Ouest - Savard, Sébastien; van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Oukouami D, Ghisleine; Michel, Jean Nephetaly (Canadian Social Work Review / Revue canadienne de service social, 2024)
De nouvelles approches axées sur la cybersanté mentale l’aide à la navigation du système, les cliniques sans rendez-vous, ainsi que les approches plus traditionnelles comme les lignes d’aide et de crise cohabitent afin de promouvoir ou d’intervenir précocement en santé mentale. Comment ces interventions répondent-elles aux besoins des francophones en contexte linguistique minoritaire alors que la communication est au coeur d’une consultation réussie? Objectif : Documenter six initiatives à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest. Méthode : Études de cas, incluant trente-six entrevues semi-dirigées auprès des autorités sanitaires, des fournisseurs de soins et des usagers. Résultats : La gratuité, l’anonymat, la rapidité, la présence des pairs travailleurs, l’absence de jugement et des démarches simples facilitent l’accès aux programmes. Parmi les limites, l’insuffisance de services en français et l’accent sur les thérapies brèves peuvent affecter la continuité des services, notamment pour les usagers francophones. Conclusion : Malgré les efforts pour améliorer l’offre de services en santé mentale aux francophones, des lacunes subsistent. L’article présente certaines stratégies qui permettraient d’améliorer l’offre de ces services. Mots-clés : Santé mentale, cybersanté mentale, initiatives novatrices, Terre-Neuve-et-Labrador, Territoires du Nord-Ouest, soins par paliers, francophones en situation minoritaire

Patient-physician language concordance and quality and safety outcomes among frail home care recipients admitted to hospital in Ontario, Canada - Seale, Emily; Reaume, Michael; Batista, Ricardo; Eddeen, Anan. Bader; Roberts, Rihannon; Rhodes, Emily; McIsaac, Daniel. I.; Kendall, Claire. E.; Sood, Manish. M.; Prud'homme, Denis; Tanuseputro, Peter (Canadian Medical Association Journal, 2022)
Background: When patients and physicians speak the same language, it may improve the quality and safety of care delivered. We sought to determine whether patient–physician language concordance is associated with in-hospital and postdischarge outcomes among home care recipients who were admitted to hospital. Methods: We conducted a population-based study of a retrospective cohort of 189 690 home care recipients who were admitted to hospital in Ontario, Canada, between 2010 and 2018. We defined patient language (obtained from home care assessments) as English (Anglophone), French (Francophone) or other (allophone). We obtained physician language from the College of Physicians and Surgeons of Ontario. We defined hospital admissions as language concordant when patients received more than 50% of their care from physicians who spoke the patients’ primary language. We identified in-hospital (adverse events, length of stay, death) and post-discharge outcomes (emergency department visits, readmissions, death within 30 days of discharge). We used regression analyses to estimate the adjusted rate of mean and the adjusted odds ratio (OR) of each outcome, stratified by patient language, to assess the impact of language-concordant care within each linguistic group. Results: Allophone patients who received language-concordant care had lower risk of adverse events (adjusted OR 0.25, 95% confidence interval [CI] 0.15–0.43) and in-hospital death (adjusted OR 0.44, 95% CI 0.29–0.66), as well as shorter stays in hospital (adjusted rate of mean 0.74, 95% CI 0.66–0.83) than allophone patients who received language-discordant care. Results were similar for Francophone patients, although the magnitude of the effect was smaller than for allophone patients. Language concordance or discordance of the hospital admission was not associated with significant differences in postdischarge outcomes.

Culture de sécurité des professionnels de santé en soins primaires : adapatation en langue française du questionnaire MOSPSC (« Medical Office Survey on Patient Safety Culture ») - Shih, C.; Buchet-Poyau, K.; Keriel-Gascou, M.; Quenon, J.-L.; Michel, P.; Touzet, S.; Chanalière, Marc (Revue d'Épidémiologie et de Santé Publique, 2022)
Contexte La culture de sécurité (CDS) rend compte de déterminants individuels et organisationnels. Son évaluation auprès des professionnels de santé en soins primaires (SP) peut être réalisée par des questionnaires auto-administrés, tel le « Medical Office Survey on Patient Safety Culture » (MOSPSC). Objectif Adapter en français le questionnaire MOSPSC et en étudier les propriétés psychométriques. Méthode Le questionnaire MOSPSC a fait l'objet d'une traduction avec analyse linguistique en langue française ; une rétrotraduction vers l'anglais a été réalisée, conformément aux recommandations de l'ISPOR. La version française du questionnaire a été diffusée à 415 professionnels de santé de 36 structures pluriprofessionnelles ambulatoires. L’étude des propriétés psychométriques (test-retest, α de Cronbach et analyse factorielle) a été conduite à partir des réponses des professionnels. Résultats Après analyse linguistique, la notion d’équipe a été traduite par celle de structure dans le questionnaire final. Le taux de participation des professionnels à l'enquête était de 64,1 % (266/415) ; 51,9 % (138/415) étaient des paramédicaux (principalement IDE ou kinésithérapeutes). Le coefficient α de Cronbach est de 0,94 pour l'ensemble des dimensions. Après analyse psychométrique, la dimension « signalement des évènements indésirables » a été ajoutée, et celle de « formation du personnel » intégrée à celle de « formation et standardisation des pratiques », portant à 13 le nombre de dimensions identifiées après analyse factorielle. Conclusion Le questionnaire MOSPSC adapté et validé en français peut être utilisé pour mesurer la CDS des professionnels en soins primaires en France. Son usage permettrait d'envisager à terme des comparaisons à l’échelle de chaque structure, pour y suivre l’évolution de la CDS, et dans le cadre de recherches nationales et internationales sur la gestion des risques en soins primaires.

Access to health and social services for Quebec’s English-Speaking Minority Communities: Recent challenges, legislative context, and research recommendations. - Shoumarova, Lina (Quebec English-Speaking Communities Research Network, 2024)

Pour une réforme de la santé respectueuse des deux communautés linguistiques officielles. Mémoire présenté à l’honorable Dorothy Shephard, ministre de la Santé, dans le cadre de la consultation publique sur l’avenir des soins de santé dans la province du Nouveau-Brunswick - Société de l'Acadie du Nouveau-Brunswick (2021)

French among Health Care Workers in Canada Outside Quebec, 2021 (Infographic) - Statistics Canada (2025)

French among healthcare workers in Canada outside Quebec, 2001 to 2016 [infographic] - Statistics Canada (2021)

French and English among Healthcare Workers in Quebec, 2021 (Infographic) - Statistics Canada (2025)

Table : 15-10-0041-01 Frequency of health care or services obtained in the minority official language, by age group and gender, for adults in the official language minority population - Statistics Canada (Gouvernement du Canada, 2025)
Health services or care in the minority official language by age group and gender, Canada, among adults in the minority official language population who considered it important to obtain health services or care in the minority official language, 2022. Possibility to conduct more specific searches for Quebec, Canada outside Quebec, certain provinces, or certain regions.

English and french among healthcare workers in Quebec, 2001 to 2016 [infographic] - Statistique Canada (2021)

Le français chez les travailleurs de la santé au Canada hors Québec, 2001 à 2016 [infographie] - Statistique Canada (2021)

Le français chez les travailleurs et travailleuses de la santé au Canada hors Québec, 2021 (infographie) - Statistique Canada (2025)

Le français et l’anglais chez les travailleurs de la santé au Québec, 2001 à 2016 [infographie] - Statistique Canada (2021)

Le français et l'anglais chez les travailleurs et travailleuses de la santé au Québec - 2021 (infographie) - Statistique Canada (2025)

Des services de santé dans ma langue, un “horizon d’attente” : Programme de santé mentale de Montfort et parcours psychiatriques. - Thifault, Marie-Claude (Le moment Monfort dans la francophonie canadienne, 2024)
fs-ref-orig: Thifault, M.-C. (2024). Des services de santé dans ma langue, un “horizon d’attente” : Programme de santé mentale de Montfort et parcours psychiatriques. Dans F. Charbonneau et M. Bock (dir.), Le moment Monfort dans la francophonie canadienne (p. 205-226). Presses de l’Université d’Ottawa. fs-code-orig: Thiffault - 2024

Dérives : une histoire sensible des parcours psychiatriques en Ontario français - Thifault, Marie-Claude; LeBel, Marie (Les Presses de l'Université d'Ottawa, 2021)
fs-ref-orig: Thifault, M.-C. et LeBel, M. (2021). Dérives : une histoire sensible des parcours psychiatriques en Ontario français. Les Presses de l'Université d'Ottawa. fs-code-orig: Thifault-2021

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

The impact of linguistic concordance and the active offer of French language services on patient satisfaction - Timony, Patrick; Gauthier, Alain; Wenghofer, Elizabeth; Hien, Amelie (Diversity of Research in Health Journal, 2022)
Communication is essential to providing quality primary care. Linguistic concordance between patients and physicians has been linked to improved health outcomes and greater patient satisfaction. Although Canadian Francophones often struggle to access linguistics concordant health services, the concept of the active offer of French Language Services (FLS) has emerged as a means of ensuring the availability of such services and improving the francophone patient experience. However, the impact of language concordance and the active offer of FLS on patient satisfaction among Ontario Francophones remain largely unknown. Patient satisfaction surveys were collected as part of a continuing education program targeted at family physicians in Northeastern Ontario. Participating physicians distributed patient surveys consisting of select patient satisfaction questions from the Physicians Achievement Review (PAR) and select questions from the Active Offer of French Language Services in Minority Context Measure. Valid surveys were received from 235 patients. Just under half of these (44%) identified as Francophones, 62.6% had a French-speaking family physician; however, only 17.2% reported regularly speaking in French with their family physician. As hypothesized, there was a consistent tendency for Francophones who experience stronger linguistic concordance with their family physician to report higher satisfaction scores. Francophones who regularly speak French with their family physicians were more satisfied ( = 4.63) than those who rarely/never speak French ( = 4.29, F(1; 83) = 4.852; p < 0.05). There was also a statistically significant interaction between the patients' language of preference and the service language. Francophones who prefer French and regularly speak it with their family physician (linguistic concordance; adj= 4.82) were significantly more satisfied than those who prefer French yet rarely/never speak it (linguistic discordance; adj= 4.06, F(1; 75) = 11.950; p < 0.001). Furthermore, a positive correlation between patient satisfaction and the active offer was observed in Francophones (r = 0.49, p<0.001). The present findings provide evidence of the impact of linguistically adapted health care services on the satisfaction of Ontario Francophones and suggest that patient satisfaction may be improved through the active offer of FLS. A larger and more diverse sample is required to confirm these findings.

Adopting a lay navigator training programme in primary care - Toal-Sullivan, Darene; Lemonde, Manon; Gauthier, Alain P.; Dahrouge, Simone (Health Education Journal, 2021)
Introduction: There is growing interest in the role and use of patient navigators within the health care system. Currently, qualifications and training expectations documented in the literature vary tremendously depending on context and patient population. This paper details the theoretical and pedagogical principles used to develop, implement and evaluate a training programme for lay patient navigators working in a primary care setting. Methods: The planning process involved (a) conducting an educational needs assessment, (b) identifying the theory underpinning the curriculum, (c) developing learning objectives and teaching strategies, (d) formulating evaluation methods, (e) implementing the programme and (f) refining the curriculum based on evaluation feedback and lessons learned. The training programme was first implemented in May 2017 and has evolved over the past 3 years based on our observations and feedback from the programme participants. Results: The training programme involves a total of 25 hours of online and face-to-face education sessions, and ongoing community mentorship from experienced navigators. All training components are rooted in theoretical principles and proven pedagogical approaches. The knowledge, skills and abilities acquired are also tied to core competencies of the role of lay patient navigator. Conclusion: The development of this lay navigator training programme was carefully designed with evidence-based competencies and practical realities to ensure rigour in preparing and supporting navigators’ work in primary care settings.

Improving access to health services in French: The power of networking and knowledge mobilization, a proven Canadian Model - Tremblay, Michel; Leis, Anne (Linguistic Minorities and Society, 2021)
Language barriers have a detrimental impact on access to health services and compromise patients’ safety. The purpose of this article is to describe and evaluate how the Société Santé en français (SSF) and the 16 French Language Health (FLH) networks used networking and knowledge mobilization for improving access to health services in French for Francophone and Acadian minority communities (FAMC). Method: Data was extracted from the 2013-2018 program’s reports and evaluation. Results confirmed that networking effectively mobilized key partners for better access to health services in French regardless of location. This access increased incrementally as a function of the customized level of support provided to the system by the SSF and the FLH networks and, to a lesser extent, when FAMC represented over 3.5% of the total population in the region, province or territory. Networking and knowledge mobilization contribute to augmenting access to safe, quality health services in French for FAMC. Keywords: access, partnership and networking, active offer, language barriers, knowledge mobilization

Pratique # 25 : Accès éQUITÉ : Simplifier l’accès aux services de santé en français (Société Santé en français) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Pratiques novatrices en santé mentale pour les populations de langue officielle minoritaire à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest - van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Savard, Sébastien; Oukouomi, G.; Michel, J. N. (Université d'Ottawa, Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (2021)
fs-ref-orig: van Kemenade, S., Michel, J.N., Savard, J. & Benoît, J. (2021, mise à jour 2025). Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https:// www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: van Kemenade-2025a

Les expériences de patients francophones qui se présentent fréquemment à l'urgence pour des raison de santé mentale - Vandyk, Amanda; Lightfoot, Sophie; Levesque, Kristine; Domecq, Marie-Cécile.; Jacob, Jean Daniel (Recherche en soins infirmiers, 2022)
Introduction: Language and communication are pivotal to the safe care and management of people with mental health disorders, particularly when these patients are linguistic minorities. Objectives/method: To explore these experiences within linguistic minority populations by completing a literature review and qualitative interviews. Interviews were conducted in Ottawa, Canada, with francophone patients. The studies included in the review represented the international literature on linguistic minorities in general. Results: Overall, the experiences described in the published articles were similar to the participants' own experiences, suggesting that barriers to care exist even in settings mandated to provide services in both official languages. Discussion/conclusion: There are many barriers to the provision of mental health care services, regardless of the dominant language. However, we identified an internalized sense of responsibility felt by linguistic minority patients, who feel compelled to compensate for or fill in the language gaps of providers. Keywords: health services accessibility; language; mental health; qualitative research; rapid review.

Création d'une grille d'observation pour simulations sur l'offre active de services de santé en français - Vincent, Coralie; Bodnaruc, Alexandra Maria; Kengneson, Cris-Carelle; Savard, Jacinthe; Giroux, Isabelle (Reflets, 2021)
Au Canada, il fut démontré que les communautés francophones vivant en situation linguistique minoritaire éprouvent des difficultés à se prévaloir de services sociaux et de santé dans leur langue de préférence, ce qui peut négativement affecter la qualité et la sécurité des services. L’offre active est une pratique visant à contrer les effets de la minorisation linguistique en invitant, de manière proactive et dès le premier contact, les bénéficiaires à s’exprimer dans la langue officielle de leur choix. Il n’existe actuellement aucun outil validé permettant l’évaluation de cette compétence auprès des futurs professionnels des domaines de la santé et des services sociaux. Cet article présente les étapes de création et de validation de Grille d’observation des indicateurs de compétence la en offre active de services en français, laquelle vise à soutenir les programmes de formation dans l’enseignement et l’évaluation de cette compétence au moyen de simulations. Mots-clés : minorités linguistiques, offre active de services en français, langue et services, qualité des soins, formation professionnelle en santé et service social, grille d’observation, validation

Do nurses use discourse markers differently when using their second language as opposed to their first while interviewing patients? - Yeji, Han; Segalowitz, Norman; Khalil, Laura; Kehayia, Eva; Turner, Carolyn; Gatbonton, Elisabeth (The Canadian Modern Language Review, 2020)
Les auteurs se demandent si l’utilisation de marqueurs discursifs change, dans les interactions des infirmières avec les patients, en fonction de l’usage qu’elles font de leur langue maternelle (L1) ou de leur langue seconde (L2). Les marqueurs sont analysés à titre de marqueurs de maintien du tour de parole, indiquant la « prise en compte » et de marqueurs de transition dans le discours, indiquant un changement de sujet ou de locuteur dans la conversation. Ces deux catégories de marqueurs diffèrent sur le plan du degré de gestion du discours et du contrôle interactionnel. Seize infirmières mènent auprès d’un patient de L1 anglaise et d’un patient de L1 française un entretien visant l’évaluation de la douleur, entretien dans lequel les infirmières utilisent leur propre L1 dans un cas et leur propre L2, moins bien maîtrisée, dans l’autre. Les résultats de l’étude ne permettent pas de confirmer la première hypothèse, selon laquelle les infirmières devraient normalement utiliser les marqueurs discursifs plus fréquemment en L1 qu’en L2. Ils confirment toutefois la seconde hypothèse, selon laquelle les infirmières devraient utiliser les marqueurs de changement de sujet moins fréquemment en L2 qu’en L1, comparativement à leur usage (de base) des marqueurs de maintien du tour de parole. Les constatations des auteurs, en particulier l’attestation de la seconde hypothèse, pourraient avoir des répercussions sur le développement de la formation en L2 des professionnels de la santé.